(3QSGdI aj GdaUOs - (3bSWG Hf dhbG GdHYdHcj,J (B300 (3g` s
(3ChdgG (B:s
(3GLgGO GdfaS ai GdhaG HGdaQGjV ChLH ef MedgG ai GdfhGad s
(3BNQgG (B:s
(3heG cGf ef GdGHOGf gPg MGdg adjS jfHZi Cf jJhba Yf YdGLg Edi Gf jXgQ ajg OdGFd GdGedGA s
(3fbdJ gPg GdfSNI ef fSNI SbjeIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B196 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B131s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdWHs